Pintura de objetos: narrativas e representações - Eisenberg, Maristela Morazes Santos (2014)
The present research consists of creating paintings and reflecting on the act of creating them during my Masters Degree time span at the UFSM. The reflection is guided mainly by the observation of how a visual narrative, set up with images unrelated to each other, can arise within the pictorial space of a still life. Anchoring my research to the referential works by Lancri (2000), Passeron (2004) and Rey (1996), my focus is directed at the ongoing work on the making of the paintings as they are made. During the making of the painting the painter doesn't necessarily predetermine its totality, or its final appearance. Along the artist's work that which is already created “converses” with the artist in such a manner that the creation process becomes a two-way road. It is along these lines that I present a study of the image of representational objects lying within the pictorial space as narrative, reflecting on the existing interaction between myself – as artist – and my poetics. I define benchmarks for the creation of my paintings by establishing a relationship between artistic practice and conceptual language, as well as exposing motivations for and paths towards the understanding of visual narrative as a possibility of artistic creation within the pictorial space.